2017
DOI: 10.1017/cem.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

The impact of opioid medications on subsequent fractures in discharged emergency department patients with peripheral vertigo

Abstract: Patients discharged from the ED with peripheral vertigo who were also being prescribed opioids had a higher hazard of subsequent fracture compared to those who were not, and the effect was much greater than among UTI patients. These results suggest that in the acutely vertiginous older patient, opioid analgesic medications should be modified, where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Using predefined search strategies and inclusion criteria, a total of 18 studies were included and 1,134 articles of unrelated literature were excluded (from a total of 600 articles from PubMed and 552 articles from EMBASE) after a detailed reading of the title, abstract, and full text, and the 18 articles included 884054 participants [3,7,9,1932]. The detailed process of inclusion in this study is shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using predefined search strategies and inclusion criteria, a total of 18 studies were included and 1,134 articles of unrelated literature were excluded (from a total of 600 articles from PubMed and 552 articles from EMBASE) after a detailed reading of the title, abstract, and full text, and the 18 articles included 884054 participants [3,7,9,1932]. The detailed process of inclusion in this study is shown in Fig 1.…”
Section: Resultsmentioning
confidence: 99%
“…The detailed process of inclusion in this study is shown in Fig 1. Five studies were from the United States [12,21,23,24,26,32], three from Canada [9,19,28], two from the United Kingdom [18,27], one study was from Australia, and the remaining came from European countries; 12 articles were from cohort studies, and six were from case-control studies. The study information is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations